Ultrahigh strength and modulus copolyamide films with uniaxially cold-drawing induced molecular orientation. (February 2017) - Luo, Longbo; Huang, Jieyang; Feng, Yan; Wang, Xu; Qin, Jiaqiang; Liu, Xiangyang
The tensile strength of polymer films is generally lower than 200 MPa. Copolyamide (CPA) films with ultrahigh strength (approximately 317–865 MPa) and high modulus (approximately 3.96–11.76 GPa) were obtained by uniaxial cold-drawing and heat treatment. The relationship between structures and properties in the orientation state was also investigated. The results of Fourier transform infrared (FTIR) spectroscopy indicate that hydrogen bonding interactions change a little with drawing. Wide-angle X-ray diffraction patterns show orientational stretch induces π–π ordered packing after drawing 100%. The tensile strength and modulus of the drawn CPA films are improved approximately 41%–173% and 9%–197% compared to undrawn films. Dichroic ratios obtained under polarized FTIR spectroscopy represent overall orientation factors. The decrease of dichroic ratios at about 3300 cm −1 and 1650 cm −1 and the increase of dichroic ratios at 1515 cm −1 prove that the orientation of macromolecular chains is improved along stretch direction. What's more, the degree of orientation is further increased after heat treatment, which is the phenomenon of spontaneous orientation. The degree of spontaneous orientation increases with the increase of cold-drawing ratio. Thus, the initial orientation in cold-drawing and spontaneous orientation during heat treatment leads to ultrahigh modulus and high strength.